PENGARUH TENAGA PENJUAL, PRODUK, DAN HARGA TERHADAP KEPUASAN NASABAH SERTA IMPLIKASINYA TERHADAP LOYALITAS NASABAH PT. BANK MAYBANK CABANG WARUNG BUNCIT - Rezzi Nanda Barizki (Jurnal Ilmiah Manajemen dan Bisnis, 2018)
This researach aims to examine and analyze the effect of salesperson, product, price and their impact to customer satisfaction as wel as its impact to customer loyalty. Population of this research  is 185 active customers of PT. Bank Maybank Warung Buncit Branch. The method used in this research is analysis of  two paths. On the first path is the influence of salesperson, product, and price to customer satisfaction. The second path is the influence of salesperson, product, price and customer satisfaction to customer loyalty. The result of this research shows that salesperson, product, and price have significant effect to customer satisfaction. This research also show that salesperson, product, price and customer satisfaction have significant effect to customer loyalty. Based on research results, to improve customer satisfaction and loyalty, company needs to improve salesperson, product and price strategy. In future researh, researcher suggested to put other variables such as word of mouth, promotion, etc.